2015
DOI: 10.1002/csr.1371
|View full text |Cite
|
Sign up to set email alerts
|

Business Strategy for Climate Change: An ASEAN Perspective

Abstract: Business operations have been severely impacted by the increasing frequency and intensity of extreme weather conditions affecting economic development. Consequently, public pressure has been directed at businesses to build resilient and sustainable operations, especially in ASEAN countries, whose fragile natural environments make them among the most vulnerable to climate change. To better understand organisational responses, this study investigated the influence of internal resources and geographical regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(119 citation statements)
references
References 73 publications
(141 reference statements)
3
111
0
5
Order By: Relevance
“…energy intensity, economic regulation). Firm specific characteristics empirically identified as causing variability in environmental strategy (González‐Benito and González‐Benito, ; Hahn and Kühnen, ; Muttakin et al ., ) and climate change strategy (Wahyuni and Ratnatunga, ; Amran et al ., ) include corporate size, internationalization, financial performance (e.g. liquidity or profitability), managerial attitude, managerial international experience, strategic direction and attitude, ownership structure, board diversity, and position in the value chain, among others.…”
Section: Discussionmentioning
confidence: 99%
“…energy intensity, economic regulation). Firm specific characteristics empirically identified as causing variability in environmental strategy (González‐Benito and González‐Benito, ; Hahn and Kühnen, ; Muttakin et al ., ) and climate change strategy (Wahyuni and Ratnatunga, ; Amran et al ., ) include corporate size, internationalization, financial performance (e.g. liquidity or profitability), managerial attitude, managerial international experience, strategic direction and attitude, ownership structure, board diversity, and position in the value chain, among others.…”
Section: Discussionmentioning
confidence: 99%
“…While pursuit of multiple strategies implies that firms engage in a range of carbon abatement actions with different levels of expected return, pursuit of a single strategy indicates rational investments in actions where the expected return is highest (Al-Amin et al, 2015;Maxwell and Decker, 2006;Petkova et al, 2013). Further, calls are increasing in the literature for an identification of factors that affect business strategies concerned with climate change (Amran et al, 2015;Christ and Burritt, 2013). These questions and motivations provide the rationale for the study reported herein.…”
Section: Climate Change Mitigation Strategymentioning
confidence: 90%
“…Prior research concerned with climate change related strategies is diverse and falls within many streams. For example, these include theoretical conceptualizations of such strategies (Boiral, 2006;Hoffman, 2005), empirical investigations of carbon reduction and other climate change related practices in firms (Cadez and Czerny, 2010;Hashmi and Al-Habib, 2012;Jeswani et al, 2008;Kolk and Pinkse, 2005;Lee, 2012;Sprengel and Busch, 2011;Talbot and Boiral, 2014;Wahyuni and Ratnatunga, 2015;Weinhofer and Busch, 2013;Weinhofer and Hoffmann, 2010), explorations of barriers, drivers, and contingencies of such strategies (Amran et al, 2015;Backman et al, 2015;Liu, 2012;Okereke and Russel, 2010;Reid and Toffel, 2009;Rickards et al, 2014;Slawinski and Bansal, 2012;Sprengel and Busch, 2011), the implications of climate change strategies for firms' economic performance (Hsu and Wang, 2013;Matsumura et al, 2014) and implications for firms' GHG emissions performance (Doda et al, 2015).…”
Section: Climate Change Mitigation Strategymentioning
confidence: 99%
“…It also questions the importance of the so-called 'home-country effect' (Levy and Kolk, 2002). If highly globalized companies with different regional affiliations exhibit similar strategy patterns, the institutional environments of a company's dominant sales markets might be more influential than home-country factors, which is called the 'host-country effect' (Amran et al, 2016). While the goal of this paper is not to test hypotheses on the relationship between institutional factors and strategies, we want to shed more light on how the regional context of a company's business affects the type of strategy employed.…”
Section: Institutional Environmentmentioning
confidence: 99%
“…However, firms from these regions are relatively evenly distributed across the clusters. Thus, their strategies seem to be influenced not solely by their home-country's institutional environment but rather by other factors, such as the framework conditions of other countries they are operating in (Amran et al, 2016). Companies that are more globalized are exposed to a greater variety of institutional settings and tend to show more ambitious action on climate change to legitimate their business (Bansal, 2005).…”
Section: Differences Between the Strategy Clustersmentioning
confidence: 99%